Analysis of Contributing Factors in Early Detection for the Prevention of Preeclampsia among Pregnant Women in Primary Health Care Settings - Maulida Nurfazriah Oktaviana; Firdawsyi Nuzula (Discover Health and Medicine, 2025)
Introduction: Preeclampsia is one of the leading causes of maternal morbidity and mortality, alongside hemorrhage and infection. Early diagnosis of preeclampsia, which is a precursor to eclampsia, is essential to reduce maternal and neonatal mortality rates. Globally, preeclampsia remains a major contributor to illness and death among mothers and infants, as it is associated with various complications affecting both the mother and the newborn. Methods: This study employed a quantitative research design using a descriptive correlational approach with a cross-sectional method to determine the relationship between birth spacing, history of preeclampsia, self-motivation, social support, and antenatal care (ANC) compliance with the risk of preeclampsia. The sampling technique used total sampling, with 90 respondents included. Data were analyzed using the Chi-square test. Results: The results showed that the variable birth spacing had a p-value of 0.133, indicating no significant relationship with the risk of preeclampsia. The history of preeclampsia variable had a p-value of 0.000, showing a significant association with preeclampsia risk. The motivation variable had a p-value of 0.441, suggesting no significant relationship with preeclampsia risk. The social support variable had a p-value of 0.345, indicating no significant relationship with preeclampsia risk. The ANC compliance variable had a p-value of 0.528 (> 0.05), showing no significant effect on preeclampsia risk. Conclusion: Mothers with a previous history of preeclampsia are at an increased risk of recurrent preeclampsia. Therefore, it is essential for these mothers to undertake preventive measures and receive regular medical monitoring to minimize potential complications.